2020
DOI: 10.1039/d0re00069h
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on plasma-assisted synthesis of N-doped nanoparticles as nanopesticides for pest control in crops

Abstract: Green plasma-based technology production of N-doped NPs for a new agri-tech revolution in pest control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 219 publications
0
12
0
Order By: Relevance
“…[19] Europe's "chemical plants of tomorrow" are envisioned as compact container plants to speed up process development and offer as well as advantages for chemical production. [20] Those plants are mobile (Evonik's "Plants on Wheels [21] " and the "50% Idea [22] " of the German chemical industry and academia) and can utilize renewable energy (Evonik's "Fertilizing with the Wind [23] "). That opens the door to entirely new business models for distributed production at the local site of farming.…”
Section: Future Factories: An Enabler For Local Manufacturingmentioning
confidence: 99%
“…[19] Europe's "chemical plants of tomorrow" are envisioned as compact container plants to speed up process development and offer as well as advantages for chemical production. [20] Those plants are mobile (Evonik's "Plants on Wheels [21] " and the "50% Idea [22] " of the German chemical industry and academia) and can utilize renewable energy (Evonik's "Fertilizing with the Wind [23] "). That opens the door to entirely new business models for distributed production at the local site of farming.…”
Section: Future Factories: An Enabler For Local Manufacturingmentioning
confidence: 99%
“…Nanoformulation or encapsulation of insecticides, herbicides, fungicides and bactericides with nanomaterials holds enormous potential for decreasing chemical pesticides doses, increasing crop production and promoting sustainable development [ 11 , 22 ]. Nanocarriers of nanopesticides include polymeric NPs (such as chitosan and solid lipids), inorganic nonmetallic NPs (such as silica NPs and nanoclays) and metallic NPs (such as Cu NPs and ZnO NPs) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Several studies have shown that nanotype insecticides are more efficient at killing pests and less likely to cause side effects on humans [ 35 ].…”
Section: Nanopesticidesmentioning
confidence: 99%
“…In recent years, growing attention has been paid to nanoscale materials research, with a particular focus on metallic nanoparticles and their applications in environmental analysis [ 40 , 41 ]. Metal nanoparticles (MNPs) have a high surface area ratio of atoms with free valences to the cluster of total atoms, which allows them to enhance and improve the activity of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%